Expression of multidrug resistance markers ABCB1 (MDR-1/ Pgp) and ABCC1 (MRP-1) in renal cell carcinoma - O'DRISCOLL, LORRAINE (My University, 2009)
Background Renal cell carcinoma patients respond poorly to conventional chemotherapy, this unresponsiveness may be attributable to multidrug resistance (MDR). The mechanisms of MDR in renal cancer are not fully understood and the specific contribution of ABC transporter proteins which have been implicated in the chemoresistance of various cancers has not been fully defined in this disease. Methods In this retrospective study the expression of two of these transporter efflux pumps, namely MDR-1 P-gp (ABCB1) and MRP-1 (ABCC1) were studied by immunohistochemistry in archival material from 95 renal cell carcinoma patients. Results In the first study investigating MDR-1 P-gp and MRP-1 protein expression patterns in renal cell carcinoma patients, high levels of expression of both efflux pumps are observed with 100% of tumours studied showing MDR-1 P-gp and MRP-1 positivity. Conclusion Although these findings do not prove a causal role, the high frequency of tumours expressing these efflux pumps suggests that they may be important contributors to the chemoresistance of this tumour type.
PUBLISHED
Keywords: Pharmacy and Pharmaceutical Sciences; Cancer